(untitled) (Bon Voyage, 2023)
This paper assesses how Parijat in her masterpiece Blue Mimosa deals with the issues of Nepalis’ global encounters. Primarily through one of the protagonists of the novel Suyogbir, Parijat weaves a story of a Nepali lahure who, in course of fighting the World War, interacts with the people abroad and brings in global experiences to his native country as he narrates the saga of his experiences with the female protagonist Sakambari. Significantly departing from her predecessors and also from her contemporaries primarily because of her serious concern with the global issues that no more affected only the people of her origin but those throughout the globe, Parijat in the novel caters to the new subjects to her readers. Her fascination with novel and experimental forms that rigorously redrew the boundaries of the traditional categories and her serious effort in familiarizing her readers with the global issues led her to the path of transcending her local experiences and thus acquiring a transnational stature. Applying Paul Jay’s ideas on transnational literature, this paper analyzes how Parijat in the novel blends the local and the global experiences with craft and imbricates those diverse experiences to constitute a beautiful structure. Her unique mixture of characters representing various cultural milieus, selection of settings and philosophical depth in subject matter blur the boundaries of ‘national’ category of writing and thus create an ambience where the local and the global intersect.